Orientação da grávida com patologia maligna do colo uterino - Ana Cláudia Martins Novais (2018)
Cervical cancer is one of the most common malignancies diagnosed during pregnancy. Despite representing a challenge, this diagnosis does not necessarily mean interruption of pregnancy. The aim of this work is to review the management of invasive cervical cancer in pregnant women, by analyzing guidelines and systematic reviews published over the last couple of decades on staging, management, time and mode of delivery and prognosis. When defining management strategies, the goal is to obtain a similar prognosis of non-pregnant women with invasive cervical cancer, while protecting the mother, fetus and newborn. Long term impact on women and descendants remains unclear.